2017
DOI: 10.32404/rean.v4i3.1400
|View full text |Cite
|
Sign up to set email alerts
|

Relação Entre O Estádio De Abertura Floral E Pulsing Na Vida Útil Do Copo De Leite

Abstract: O copo de leite é muito apreciado tanto como flor para uso em arranjos florais bem como em jardins, contudo, os aspectos relacionados à determinação do ponto de colheita e o prolongamento da sua vida útil pós-colheita ainda são bem escassos na literatura. Diante disso o presente trabalho tem por objetivo avaliar a relação entre o estádio de abertura floral das espatas de copo de leite e a sua conservação em solução de pulsing a base de ácido cítrico. Para tanto adotou-se um delineamento experimental inteiramen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The withering and yellowing of the leaves, in general, began after nine days of preservation, and it was accentuated from 15 days, period that also the senescence of the central inflorescences of floral stem of safflower intensified, presenting score three (Figure 3) of quality scale aforementioned. Evidences of senescence similar to the one of this work were verified by Bellé et al (2004) for chrysanthemum from 10 days of preservation postharvest in different solutions and, Sanches et al (2017) verified evidences of senescence of calla lily from 8 days of preservation in solutions for floral opening. In relation to the efficiency of the preservative solutions, we observed that the mass loss of floral stems of safflower preserved in solution of distilled water + sucrose 2% was the one that obtained the greatest acceleration of deterioration in comparison to the other ones, reaching loss on average of 46% at six days of preservation for all the seasons.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The withering and yellowing of the leaves, in general, began after nine days of preservation, and it was accentuated from 15 days, period that also the senescence of the central inflorescences of floral stem of safflower intensified, presenting score three (Figure 3) of quality scale aforementioned. Evidences of senescence similar to the one of this work were verified by Bellé et al (2004) for chrysanthemum from 10 days of preservation postharvest in different solutions and, Sanches et al (2017) verified evidences of senescence of calla lily from 8 days of preservation in solutions for floral opening. In relation to the efficiency of the preservative solutions, we observed that the mass loss of floral stems of safflower preserved in solution of distilled water + sucrose 2% was the one that obtained the greatest acceleration of deterioration in comparison to the other ones, reaching loss on average of 46% at six days of preservation for all the seasons.…”
Section: Resultssupporting
confidence: 84%
“…SC1: distilled water (control); SC2: distilled water + 2% sucrose; SC3: distilled water + 2% sodium hypochlorite and SC4: distilled water + 2% sucrose + 2% sodium hypochlorite. Castro et al (2014) and Sanches et al (2017) point that the longevity of floral stems is directly related to the stage of development of the flowers in the harvest, that is, the opening point, in which the more the flower bud is open, the lower will be its durability in vase, in virtue of the acceleration of metabolic process of breathing, being necessary the use of preservative solutions for maintaining the floral quality by a greater period of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calla lilies are usually harvested when they show extended spathes (Almeida et al, 2009); however, different harvest stages have been recently accepted for use in decoration. Harvesting at earlier stages (closed or partial opening) can provide inflorescences with better quality and longevity (Carneiro et al, 2014;Sales et al, 2015;Mattos et al, 2017, Sanches et al, 2017, Sales et al, 2018, Nascimento et al, 2019. However, limited information is available on the influence of chemicals in the storage solution on the longevity and water relations of early harvested floral stems.…”
Section: Introductionmentioning
confidence: 99%